Technology use and attitudes towards digital mental health in people with severe mental health problems: a survey study in China - Zhang, Xiaolong; Lewis, Shôn; Chen, Xu; Berry, Natalie; Bucci, Sandra (Frontiers in Psychiatry, 2023)
Introduction: Digital mental health is a promising solution to support people with severe mental health problems (SMI) in China. However, little is known about the ownership rate of digital technologies and attitudes towards utilising digital health technologies (DHTs) among people with SMI in the Chinese context. The aims of this study were to understand: (i) digital technology ownership and usage rate of people with SMI in China; (ii) attitudes toward DHTs in mental health services; and (iii) how the COVID-19 pandemic has influenced views on digital mental health.Methods: A cross-sectional survey was given to outpatients with SMI using the REDCap platform. To capture a diverse sample of people with SMI, the survey was distributed across psychiatric hospitals, general hospitals with a psychiatric unit, secondary hospitals, and community healthcare centres.In total, 447 survey respondents completed the survey. Relative high ownership rates of digital technologies were found, with smartphone ownership (95.5%) and access to the internet (82.1%) being the highest technologies reported. However, less than half of respondents reported frequent health-related usage of digital technologies, which may be related to the lack of knowledge in using DHTs. Most respondents found DHTs being useful for access to mental health services during the pandemic and were willing to use DHTs after the pandemic. Discussion: Our data suggest that, despite the high ownership rate of digital technologies, training programmes to improve digital health literacy for people with SMI in China are necessary to realise the full potential of digital mental health.